DESAIN PEMBELAJARAN SISTEM PERSAMAAN LINEAR DUA VARIABEL MELALUI CONTEXTUAL TEACHING AND LEARNING - Muhammad Iqbal; Sukirwan Sukirwan (Jurnal Lebesgue : Jurnal Ilmiah Pendidikan Matematika, Matematika dan Statistika, 2023)
This research aims to comprehend how the context of buying and selling activities and a hypothetical learning trajectory (HLT) can aid in learning two-variables linear equation system through contextual teaching and learning (CTL) in class 8.1 and in class 8.3 at Madrasah Sanawiah al-Mubarok. The research method used is design research. The essential characteristic of design research is the cycle. The research subjects for the first cycle (preliminary teaching) included 28 students from class 8.1. In this cycle the first HLT is being tested to observe students as they progress through the learning trajectory. The revised HLT will be implemented in the second cycle (teaching experiment). The research subjects for the second cycle included 33 students from class 8.3. The obtained data are analyzed qualitatively. The results of the retrospective analysis indicate that the use of buying and selling activity contexts can facilitate students’ understanding of how the two-variables linear equation system is applied to solve related problems. According to the retrospective analysis results, 1) using context of buying and selling activities can aid students in comprehending how to apply the two-variables linear equation system to solve related problems; 2) the HLT in learning the two-variables linear equation system through CTL includes learning objectives, activities that occur during learning, and student answer hypotheses. The learning trajectory used includes making meaningful connections; engaging in significant activities; achieving high standards; self-regulated learning; nurturing and fostering student personalities; critical and creative thinking; collaboration; authentic assessment